Influence of electrode positioning on accuracy and reproducibility of electrical velocimetry cardiac output measurements - Trinkmann, Frederik; Michels-Zetsche, Julia D.; Dösch, Christina; Weiß, Christel; Schönberg, Stefan; Akın, Ibrahim; Borggrefe, Martin; Papavassiliu, Theano; Saur, Joachim (Physiological measurement, 2016)
Electrical velocimetry (EV) is one of the most recent adaptions of impedance cardiography. Previous studies yielded diverging results identifying several factors negatively influencing accuracy. Although electrode arrangement is suspected to be an influencing factor for impedance cardiography in general, no data for EV is available. We aimed to prospectively assess the influence of electrode position on the accuracy and reproducibility of cardiac output (CO) measurements obtained by EV. Two pairs of standard electrocardiographic electrodes were placed at predefined positions of the thorax in 81 patients. The inter-electrode gap was varied between either 5 or 15 cm by caudal movement of the lowest electrode. Measurements were averaged over 20 s and performed twice at each electrode position. Reference values were determined using cardiac magnetic resonance imaging (CMR). Mean bias was 1.2 ± 1.6 l min−1 (percentage error 22 ± 28%) between COCMR and COEV at the 5 cm gap significantly improving to 0.5 ± 1.6 l min−1 (8 ± 28%) when increasing the gap (p < 0.0001). The mean difference between repeated measurements was 0.0 ± 0.3 l min−1 for the 5 cm and 0.1 ± 0.3 l min−1 for the 15 cm gap, respectively (p = 0.3). The accuracy of EV can be significantly improved when increasing the lower inter-electrode gap still exceeding the Critchley and Critchley recommendations. Therefore, absolute values should not be used interchangeably in clinical routine. As the reproducibility was not negatively affected, serial hemodynamic measurements can be reliably acquired in stable patients when the electrode position remains unchanged.